Molecular Imaging of Heart Failure : An Update and Future Trends - Saraste, Antti (Elsevier, 2025)
Molecular imaging can detect and quantify pathophysiological processes underlying heart failure, complementing evaluation of cardiac structure and function with other imaging modalities. Targeted tracers have enabled assessment of various cellular and subcellular mechanisms of heart failure aiming for improved phenotyping, risk stratification, and personalized therapy. This review outlines the current status of molecular imaging in heart failure, accompanied with discussion on novel developments. The focus is on radionuclide methods with data from clinical studies. Imaging of myocardial metabolism can identify left ventricle dysfunction caused by myocardial ischemia that may be reversible after revascularization in the presence of viable myocardium. In vivo imaging of active inflammation and amyloid deposition have an established role in the detection of cardiac sarcoidosis and transthyretin amyloidosis. Innervation imaging has well documented prognostic value in predicting heart failure progression and arrhythmias. Tracers specific for inflammation, angiogenesis and myocardial fibrotic activity are in earlier stages of development, but have demonstrated potential value in early characterization of the response to myocardial injury and prediction of cardiac function over time. Early detection of disease activity is a key for transition from medical treatment of clinically overt heart failure towards a personalized approach aimed at supporting repair and preventing progressive cardiac dysfunction.